Alcohol Consumption Motivation in Adolescents - Yudisa Diaz Lutfi Sandi; Lina Nurul Hidayati; Hamidatus Daris (STIKes Patria Husada Blitar, 2021)
The number of alcoholic drinks that adolescents abuse was due to various reasons. The objective of the study was to explore the motivation of adolescents in consuming alcohol. This study used a qualitative descriptive method. 13 participants were selected according to the inclusion criteria using snowball sampling. The data collection used semi-structured interviews. The data analysis stage in this study used the Colaizzi technique. This study consisted 3 main themes and 19 sub-themes; (1) feelings: a) comfortable, b) happiness, c) relieved, d) satisfied; (2) encouragement: a) society, b) curious, c) addictive, d) friend invitation, e) escape, f) solidarity, g) got trouble, h) stimulate activity, i) looking for new experience; (3) achievement: a) got many friends, b) recognized, c) so it looks cool, d) he problem solved, e) able to tell stories, f) healthy in body. The consumption of alcohol in adolescents was based on the will of the adolescent, both from within the individual and from outside the individual which motivated adolescents to consume alcohol with a purpose that the individual believes. Alcohol abuse among adolescents is a chronic problem in the government's efforts to reduce numbers due to the effect of alcoholic drinks. Alcoholic drink is a type of drink that has an intoxicating effect, is dependent on nature and causes changes in behavior, perceptions, emotions and cognition for those who consume it